Case Report: Kawasaki Shock Syndrome With Polycyclic Eruption: A Peculiar Brain Imaging - Masiello, Enrico; Buonsenso, Danilo; Lazzareschi, Ilaria; Gatto, Antonio; Piastra, Marco; Chiaretti, Antonio; Valentini, Piero (Frontiers in Pediatrics, 2021)
Kawasaki disease (KD) is a childhood vasculitis of unknown etiology. The present study describes a case of KD shock syndrome (KDSS) occured in an infant (age, 16 months) following 7 days of high fever and persistent target-like purpuric rash. Because of neurological manifestations with altered consciousness and irritability a brain MRI was perfomed, showing inflammatory involvement at level of anterior perforated substance and ipothalamus . Cerebral involvement on brain MRI rarely is described in KD but when reported is characterized mostly by cerebral vasculitis .We illustrate for the first time in KD an inflammation of the brain not related to vasculitis with peculiar neuroradiological findings. This last aspect has fascinated us in light of the recent evidences about immunological spectrum of MIS-C (Multisystem Inflammatory Syndrome in Children) and Kawasaki-like syndrome in SARS-CoV2 outbreak.